The indications and donor-site morbidity of tibial cortical strut autografts in the management of defects in long bones. (May 2018) - Lauthe, O.; Soubeyrand, M.; Babinet, A.; Dumaine, V.; Anract, P.; Biau, D. J.
Abstract : Aims: The primary aim of this study was to determine the morbidity of a tibial strut autograft and characterize the rate of bony union following its use. Patients and Methods: We retrospectively assessed a series of 104 patients from a single centre who were treated with a tibial strut autograft of > 5 cm in length. A total of 30 had a segmental reconstruction with continuity of bone, 27 had a segmental reconstruction without continuity of bone, 29 had an arthrodesis and 18 had a nonunion. Donor-site morbidity was defined as any event that required a modification of the postoperative management. Union was assessed clinically and radiologically at a median of 36 months (IQR, 14 to 74). Results: Donor-site morbidity occurred in four patients (4%; 95% confidence interval (CI) 1 to 10). One patient had a stress fracture of the tibia, which healed with a varus deformity, requiring an osteotomy. Two patients required evacuation of a haematoma and one developed anterior compartment syndrome which required fasciotomies. The cumulative probability of union was 90% (95% CI 80 to 96) at five years. The type of reconstruction (p = 0.018), continuity of bone (p = 0.006) and length of tibial graft (p = 0.037) were associated with the time to union. Conclusion: The tibial strut autograft has a low risk of morbidity and provides adequate bone stock for treating various defects of long bones. Cite this article: Bone Joint J 2018;100-B:667–74.